PROSPECTS OF RELATIONS OF UZBEKISTAN AND AZERBAIJAN: NEW HORIZONS OF COOPERATION (Web of Teachers: Inderscience Research, 2024)
This article analyzes the current and future directions of cooperation between the states of Uzbekistan and Azerbaijan. The dynamics of the development of bilateral relations in the political, economic, transport-logistics and cultural-humanitarian spheres and future opportunities are studied on the basis of a scientific approach.